Use addition to solve the linear system of equations. Include all of your work in your final answer. 3x-y=6 and y=x-4

Question

Use addition to solve the linear system of equations. Include all of your work in your final answer. 3x-y=6 and y=x-4

in progress 0
Sadie 2 weeks 2021-11-23T13:26:20+00:00 2 Answers 0

Answers ( )

    0
    2021-11-23T13:27:45+00:00

    Answer:

    x = 1, y = -3

    Step-by-step explanation:

    So, we have two equations to start with: 3x-y=6 and y = x-4, we want to resolve the equations by addition.

    We sum up the left sides of the equations together and the right sides together, and simplify, we have:

    3x – y + y = 6 + x – 4

    3x = 2 + x ==> 2x = 2 ==> x = 1

    To find y, we place the value of x in any of the two equations:

    y = x – 4 = 1 – 4 = -3

    You verify that the solution is valid by entering the values of x and y in the other equation:

    3x – y = 6 becomes

    3 (1) – (-3) = 6

    3 + 3 = 6

    0
    2021-11-23T13:28:01+00:00

    Answer:

    x = 1 and y = -3

    Step-by-step explanation:

    The given linear equations are,

    3x – y = 6 and y = x – 4

    To solve the system of equations

    Let 3x – y = 6   —–(1)

    y = x – 4

    x – y = 4  —-(2)

    (2) * -3 ⇒ -3x  + 3y = -4   —-(3)

    (2) + (3) ⇒

    3x – y = 6  

    -3x  + 3y = -12

    0   +2y = -6

    y = -6/2 = -3

    x – y = 4  

    x = 4 + y = 4 + -3 = 1

    x = 1 and y = -3

Leave an answer

Browse
Browse

27:3+15-4x7+3-1=? ( )